Delay limited communication of mobile node with wireless energy harvesting : performance analysis and optimization - Niyato, Dusit (2013)
Wireless energy harvesting is a promising feature to provide energy supply to a wireless device. However, such wireless energy supply to a mobile node is random due to mobility. In this paper, we consider performance analysis and optimization for the mobile node with delay limited communication and wireless energy harvesting capability. Three major issues are considered, i.e., optimal transmission policy for the mobile node, energy management strategy and deployment of wireless power sources. Firstly, the constrained Markov decision process (CMDP) model is formulated and solved to obtain the optimal packet transmission policy to minimize the loss probability due to delay deadline violation. Secondly, the distributed energy management strategy of the wireless power source is analyzed. Specifically, the threshold-based strategy is considered, where the wireless power source releases wireless energy only when there are a certain number of mobile nodes in its harvesting coverage. Thirdly, the wireless power sources can be optimally deployed to minimize the long-term cost composed of deployment and power consumption costs. The analysis and optimization are presented in the unified framework which can be applied to the above issues jointly.